EGR1 Is a Critical Gene in Response of Human Keratinocyte to Blue Light Radiation: EGR1 Is a Critical Gene in Response to Blue Light Radiation - Hamzeloo-Moghadam, Maryam; Rezaei-Tavirani, Mostafa; Razzaghi, Mohhamadreza; Rezaei Tavirani, Sina; Safari-Alighiarloo, Nahid; Arjmand, Babak; Rostami Nejad, Mohammad (Journal of Lasers in Medical Sciences, 2021)
Introduction: Investigating the molecular mechanism of cellular response to light radiation has attracted many researchers’ attention. In the present study, the critically affected gene by 1-hour blue light radiation in human keratinocytes was investigated via network analysis. Methods: Gene expression profiles of human keratinocytes exposed to 1-hour blue light radiation plus controls were extracted from Gene Expression Omnibus (GEO). The significantly dysregulated genes plus 100 first neighbors were investigated by Cytoscape software and its applications. The central nodes of the network based on four centrality parameters were determined and discussed. Results: Among 6 significant dysregulated genes, 4 individuals were recognized by the STRING database. The network was constructed by using the 4 queried genes and 100 first neighbors. EGR1, STAT1, and ISG15 were identified as central nodes; however, the prominent role of EGR1 was highlighted. Conclusion: EGR1 appeared as a critically affected gene after blue light irradiation. It seems that this upregulated gene is responsible for protecting human keratinocytes against stress and cancer. Therefore, the application of blue light may be accompanied by antistress effects in the human body. DOI: 10.34172/jlms.2021.83.